Health hazards resulting from exposure to heavy metals generated during the incineration of electronic and electrical waste in developing countries on the example of Agbogbloshie - Ewa Zieliński; Adriana Wielgus; Katarzyna Sas; Walery Zukow (Kazimierz Wielki University, 2018)
Combustion of electro-waste is one of the basic methods of e-waste processing in developing countries. When burning mobile phones, computers, TVs, cables and household appliances, toxic fumes containing acid gases, polycyclic aromatic hydrocarbons (PAHs), dioxins and heavy metals are released into the atmosphere and the soil. Personal air samples collected from workers and the environment air samples in Agbogbloshie indicated elevated levels for aluminum, copper, iron, zinc and lead. The article discusses the negative effects of exposure to the some indicated most dangerous heavy metals for human health.